E.04 Coma and delirium are associated with low levels of brain tissue oxygen in critically ill patients. (17th June 2016) - Wood, MD; Maslove, D; Muscedere, J; Boyd, JG
Abstract : Background: The cause of ICU delirium is unknown. We used near infrared spectroscopy (NIRS) to measure brain tissue oxygenation (BtO2) in critically ill patients, to test the hypothesis that poor cerebral oxygen delivery contributes to ICU delirium.Methods: Adult patients were enrolled if they required mechanical ventilation for >24 hours, and/or vasoactive agents. Patients were excluded if they had previous cognitive dysfunction, brain injury on admission, or a life expectancy <24 hours. BtO2 was measured for the first 24 hours of ICU admission. The confusion assessment method-ICU (CAM-ICU) was used to screen for delirium. Participants were designated to one of three groups on the basis of their predominant neurological status (comatose, delirious, or intact).Results: To date, 47 patients have been recruited. Both delirious and comatose patients' had significantly lower BtO2 levels compared to intact patients (P<0.001). There was a significant correlation between hemoglobin and BtO2 (R2=0.347, P<0.01). However, when correlation analysis was conducted separately amongst the three groups, the delirious patients (R2=0.485, P<0.05) were the strongest contributors to this positive correlation.Conclusions: Delirious patients exhibited the lowest BtO2 recordings and demonstrated a significant association between Hb and BtO2. This study offers potential insight into the pathophysiology of ICU delirium.